Détermination de l’accrétion de Calcium par des mesures externes de 47Ca - Harmut, M.; Popovic, S.; Jovanovic, V.; Simonovic, I. (Nuklearmedizin - NuclearMedicine, 1969)
The possibility of determining the calcium accretion rate by external measurements of the forearm activity and by plasma activity measurements was investigated. On the basis of these measurements and the Bauer kinetic model the index of accretion rate in the measured part of the forearm was determined. The values obtained were compared with the whole-body accretion rate values. It was found that the correlation coefficient for the body accretion rate reduced to 1 kg body weight was 0.961. The possibility of using the index of the accretion rate for the determination of the whole-body accretion rate is discussed as well as the advantages and disadvantages of determining the body accretion rate in this way.